Exploring the effects of content-based instruction on skill development, domain-specific knowledge and metacognition in the L2 - Yalçın, Şebnem. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2007., 2007)
The study investigates the effects of Content-based instruction on language, content learning, metacognitive awareness in L1 and L2 on first year students who study in a Department of Foreign Language Education at an English-medium university in Turkey. Although CBI has been investigated extensively across various contexts such as immersion and English as a second language, there is a limited documented literature in English as a foreign language context such as Turkey. Since most of the studies come from immersion and ESL, studies conducted in the EFL context are needed to explore the efficacy of CBI in EFL. The present study has an experimental research design in which 60 participants were randomly assigned to two groups. The experimental and the control group consisted of thirty participants. The participants attended follow-up sessions conducted for two hours a week in relation to a departmental course designed for improving research and study skills. Experimental group was given a treatment which is based on a syllabus design which integrated language and content for 12 weeks and the control group followed the regular follow-up syllabus. The syllabus designed for the experimental group aimed to provide a deeper treatment of the content. Thus, reading comprehension questions involved analysis and synthesis of information not only within iv a given text, but also across multiple texts. On the other hand, the control group followed a syllabus which focused on language. A set of instruments were used to measure the variables in the research questions. A multiple choice test and two essays of the participants were used to measure content learning, reading component of IELTS and two essays were used to measure language proficiency. In addition to content learning and L2 language proficiency, metacognitive awareness in L1 and L2 were also measured through questionnaires. The results of the statistical analysis revealed that CBI group outperformed the control group in content learning on both measurements but achieved as well as the control group on language proficiency again on both measurements. However, there was no statistical difference between the two groups on metacognitive awareness in L1 and L2. The results of the present study confirm the previous research which documented that language and content integration can result in better content learning. The participants in the experimental group were significantly better in content learning and were able to compete with the control group on language proficiency. These results indicate that the content learning do not end in failure in language proficiency. These results are consistent with Krashen’s hypothesis that when the focus of instruction is on meaning rather than language, success in L2 learning is achieved and with the argument that the meaningful communication in purposeful social and academic contexts provided by content and language integration is better for language learning.
Keywords: English language -- Study and teaching -- Foreign speakers.; Language and languages -- Study and teaching.; Language arts -- Correlation with content subjects.; Metacognition.